Simplified Triceps Surae Muscle Volume Assessment in Older Adults - Karamanidis, Kiros; Epro, Gaspar; König, Matthias; Mersmann, Falk; Arampatzis, Adamantios (Frontiers in Physiology, 2019)
Triceps surae (TS) muscle volume can be estimated in young adults by only considering the maximal anatomical cross-sectional area (ACSAmax) and the length of the muscle due to the presence of a constant muscle-specific shape factor. This study aimed to investigate if this simplified muscle volume assessment is also applicable in older adults or if muscle-specific shape changes with ageing. MRI sequences were taken from the dominant leg of twenty-one older female adults. The boundaries of all three TS muscles (SOL, soleus; GM, gastrocnemius medialis; GL, gastrocnemius lateralis) were manually outlined in transverse image sequences and muscle volume for each muscle was calculated as the integral of the obtained cross-sectional areas of the contours along the whole length of the muscle (measured volume) and, in addition, by using the average muscle-specific shape factors of each muscle obtained from the ratio of the measured volume and the product of ACSAmax and the muscle length (estimated volume). There were no differences in the measured and estimated muscle volumes (SOL: 357.7 ± 61.8 cm3 vs. 358.8 ± 65.3 cm3; GM: 179.5 ± 32.8 cm3 vs. 179.8 ± 33.3 cm3; GL: 90.2 ± 15.9 cm3 vs. 90.4 ± 14.8 cm3). However, when using the reported shape factors of younger adults instead, we found a significant (P < 0.05) overestimation of muscle volume for SOL and GM with average RMS differences of 6.1% and 7.6% respectively. These results indicate that corrections of muscle-specific shape factors are needed when using the previously proposed simplified muscle volume assessment as ageing may not only be accompanied with muscle atrophy, but also changes in the shape of skeletal muscle.